Raman spectra of ionic liquids: interpretation via computer simulation. - Madden, P; Wilson, M; Hutchinson, F (2004)
Theoretical Raman spectra of the complex-forming ionic liquids LaCl3 and ScCl3, derived from molecular dynamics computer simulations, are presented. These simulations, which use polarizable ion interaction models, have previously been shown to predict structural properties in excellent agreement with diffraction experiments. The dependence of the polarizability of the melt on the ionic positions, which determines the Raman spectrum through the time dependence of the polarizability correlation function, is modeled on the basis of ab initio electronic structure calculations carried out on alkali chlorides. New simulation techniques are introduced in order to allow the spectrum to be calculated with acceptable statistics. The calculated spectra are in semiquantitative agreement with experimental data. The distinctive bands which appear in the spectra of such complex melts are linked to the vibrations of the transient coordination complexes which form in these melts and new interpretations for the origin of several well-known features are proposed. The simulations thus enable a link between the structure of a melt as perceived through Raman spectroscopy and through diffraction experiments to be made.